Estrogen Biosynthesis and Action in Ovarian Cancer - Mungenast, Felicitas; Thalhammer, Theresia (Frontiers in Endocrinology, 2014)
Ovarian cancer is still the deadliest of all gynecologic malignancies in women worldwide. This is attributed to two main features of these tumors, namely, i) a diagnosis at an advanced tumor stage, and, ii) the rapid onset of resistance to standard chemotherapy after an initial successful therapy with platin- and taxol-derivatives. Therefore, novel targets for an early diagnosis and better treatment options for these tumors are urgently needed. Epidemiological data show that induction and biology of ovarian cancer is related to life-time estrogen exposure. Also experimental data reveal that ovarian cancer cells share a number of estrogen regulated pathways with other hormone-dependent cancers, e.g. breast and endometrial cancer. However, ovarian cancer is a heterogeneous disease and the subtypes are quite different with respect to mutations, origins, behaviours, markers and prognosis and respond differently to standard chemotherapy. Therefore, a characterization of ovarian cancer subtypes may lead to better treatment options for the various subtypes and in particular for the most frequently observed high-grade serous ovarian carcinoma. For this intention, further studies on estrogen-related pathways and estrogen formation in ovarian cancer cells are warranted. The review gives an overview on ovarian cancer subtypes and explains the role of estrogen in ovarian cancer. Furthermore, enzymes active to synthesize and metabolize estrogens are described and strategies to target these pathways are discussed.